2008
DOI: 10.1093/aob/mcn181
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biochemistry vs. Population Membership on Floral Scent Profiles in Colour Polymorphic Hesperis matronalis

Abstract: Shared biochemistry alone cannot explain the variation in floral scent phenotype found for H. matronalis. Such a result may suggest that the biochemical association between floral scent and floral colour is complex or dependent on genetic background. Floral scent does vary significantly with population membership; several factors, including environmental conditions, founder effects and genetics, may account for this differentiation and should be considered in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 57 publications
4
41
1
Order By: Relevance
“…While this study provides explicit measurements of neutral and selective contributions of microbial communities of flowers in the presence and absence of pollinators, it also highlights that most of the variation in community composition of floral microbiomes remains unexplained. Factors outside the flower (including soil chemistry) could affect the local pool of microbes or even the floral chemistry (Majetic, Raguso, & Ashman, ; Meindl, Bain, & Ashman, ). Similarly, variation across flowers, across plants, or even within a single plant due to competition and strong priority effects (e.g., Peay, Belisle, & Fukami, ) could be contributing to the unexplained effects and unfortunately, much of that variation is obscured in this study because to obtain enough DNA we had to pool together the organs of three different flowers from the same cage for each sample.…”
Section: Discussionmentioning
confidence: 99%
“…While this study provides explicit measurements of neutral and selective contributions of microbial communities of flowers in the presence and absence of pollinators, it also highlights that most of the variation in community composition of floral microbiomes remains unexplained. Factors outside the flower (including soil chemistry) could affect the local pool of microbes or even the floral chemistry (Majetic, Raguso, & Ashman, ; Meindl, Bain, & Ashman, ). Similarly, variation across flowers, across plants, or even within a single plant due to competition and strong priority effects (e.g., Peay, Belisle, & Fukami, ) could be contributing to the unexplained effects and unfortunately, much of that variation is obscured in this study because to obtain enough DNA we had to pool together the organs of three different flowers from the same cage for each sample.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zucker et al () found that removal of petal pigments by antisense suppression of the flavanone 3‐hydroxylase gene in the anthocyanin biosynthetic pathway led to higher emission of an aromatic volatile in Dianthus caryophyllus L. Generally, different flower color morphs in polymorphic plants show different floral scent profiles (Zucker et al, ; Majetic et al, ; Salzmann & Schiestl, ; Delle‐Vedove et al, ). Some researchers predict that flower color and scent association will be an interesting theme in pollination ecology because the understanding of relationships between floral colors and floral scents is still in its infancy (Majetic et al, ; Rausher, ; Schaefer & Ruxton, ; Dormont et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a change of floral color may impact floral scent emission level or composition and other floral characters, such as nectar profiles, visitor preference, and breeding systems, etc. Regrettably, understanding color–floral scent associations is still in its infancy, because biochemical pathways have not been researched in sufficient detail (Majetic et al, , ; Salzmann & Schiestl, ; Delle‐Vedove et al, ).…”
mentioning
confidence: 99%
“…We read absorbance at 530 nm on a Spectronic 21D spectrophotometer (Model DV #332278, Milton Roy, Rochester, NY); a higher absorbance value reflects darker purple flowers. We sampled floral scent using dynamic headspace extraction and gas chromatography‐mass spectroscopy as in Majetic et al . (2008) for day‐access plants in the morning and night‐access plants at night.…”
Section: Methodsmentioning
confidence: 99%
“…1995; Majetic et al . 2007; Majetic, Raguso & Ashman 2008) known to be attractive to the insect taxa (Dobson 2006) that visit its flowers during day and night (Mitchell & Ankeny 2001; Majetic 2008). We conducted a three‐part study focusing on the fitness effects of floral scent emission while controlling for flower colour: a scent augmentation experiment, an array experiment where we manipulated pollinator‐access, and an observational experiment across several large wild populations.…”
Section: Introductionmentioning
confidence: 99%